Chronicle of King Galawdewos (1540-1559) - Gebreyes, Solomon (Corpus scriptorum Christianorum Orientalium, 2019)
The Chronicle of King Gälawdewos (r. 1540?1559), reporting the nineteen years of the king's reign, is one of the most useful and significant historical sources for the history of Christian-Muslim relation in the sixteenth century of Ethiopia and the Horn. It represents a peculiar text in Ge'ez historiography both because of its narrative structure and the underlying sources used by the chronicler. Numerous Arabisms appear in the text, which eventually suggest that the Chronicle was written by a person with an outstanding knowledge of Arabic, in 1561. The book presents a new critical edition based on all available manuscripts and provides some detailed introductory notes and an English translation. The new edition yields philological findings concerning the Chronicle of King Gälawdewos in particular and new inputs that call for re-editing the Ethiopian royal chronicles in general. It also adds valuable by now not recorded items for Ge'ez lexicography and corrects historical distortions resulted from the previous edition. Above all, the work provides a text-critically established edition of the Chronicle of King Gälawdewos accompanied by an up-to-date concisely annotated translation, which offer new insights into the late medieval history and historiography of Ethiopia and the Horn of Africa.